A wide-bandgap conjugated polymer for highly efficient inverted single and tandem polymer solar cells. Issue 34 (10th August 2016) - Guo, Bing; Guo, Xia; Li, Wanbin; Meng, Xiangyi; Ma, Wei; Zhang, Maojie; Li, Yongfang
Abstract : Polymer solar cells based on a wide-bandgap polymer exhibited PCEs of 7.7% and 10.3% for single and tandem devices, respectively. Abstract : We synthesized a wide-bandgap conjugated polymer (namedPTZ1 ) based on thienyl-substituted benzodithiophene as the donor unit and thiazolothiazole as the acceptor unit for photovoltaic applications. The polymer exhibits a desirable broad bandgap of 1.97 eV with the maximum absorption edge of 630 nm, a deep highest occupied molecular orbital (HOMO) energy level of −5.31 eV and a relatively high hole mobility of 3.86 × 10 −3 cm 2 V −1 s −1 . Consequently, single junction PSCs based onPTZ1 exhibit outstanding performance with a PCE of 7.7% and a high V oc of 0.94 V, which are among the highest values for PSCs based on conjugated polymers with a broad bandgap near to 2.0 eV. The excellent performance is attributed to the high polymer crystallinity, favorable backbone orientation and continuous interpenetrating network in blend films. The tandem PSCs based onPTZ1 as the donor material in the front cell exhibited a high PCE of 10.3% with a V oc of 1.65 V.